Penerapan Decision Tree Pada Penentuan Waralaba - Evy Priyanti (Universitas Bina Sarana Informatika Kota Sukabumi, 2023)
Data mining is the process of extracting data into useful information. The extraction process in data mining itself consists of several parts including classification, estimation, prediction, cluster, and association. To get the best results from a data required an algorithm that processes the data. The algorithm that will be used is a decision tree or decision tree. Decision tree or decision tree is data mining with classification where the algorithm has simple rules that can make it easier and can handle noisy data and missing values. In this study using franchise data to obtain the best location for a franchise. This Franchise data is processed using a Decision tree where the accuracy results obtained are 81%. These results indicate that the level of reliability and reliability is very consistent. Franchising is currently very mushrooming and is a very good prospect for business development during the current pandemic. For this reason, a good analysis is needed to be able to determine the right type and location of the franchise, so that the profits can be maximized. To be able to obtain greater opportunities than other competitors.